Media and parliament in the Third Republic: a study of newspaper coverage of parliament by the Times of Zambia and the Post from January to November 2001 - Djokotoe-Gliguie, Edem K (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2003)
The press is credited with playing a central role in the consolidation of democracy by informing citizens, engaging them in the process of public decision making and governance and stimulating wide and inclusive debate on public matters. In emergent democracies like Zambia, the extent of the media's role as a public sphere, not to mention its impact, is not known. The study set out to investigate the extent of the press' public sphere role, particularly how Zambian newspapers report Parliament and how such coverage informs public opinion. It found that though the press covers Parliament, the nature of coverage does not empower newspaper readers with the kind of context, background and interpretation they would otherwise need to engage in public discourses on matters that affect them from an informed perspective. In the main, the role of the press in informing citizens is not fully realised, not only because uninformative character of coverage, but partly because of low literacy levels and the limited reach of local newspapers. It was against this background that the study recommended ways in which the Zambian press could re-focus its approach to parliamentary news coverage to make it more informational and more inclined towards playing a public sphere role, at least to the newspaper-reading public. Making parliamentary coverage an integrated newsroom function was the main recommendation. It provided the basis for suggesting a practical editorial option for the coverage of the legislature that accommodates the integration of context, background and interpretation into parliamentary news.
Keywords: Newspapers -- Zambia; Mass media -- Political aspects -- Zambia; Zambia -- Politics and government